Thoughts on Islamic Education According to Classical Muslim Figures (Ibnu Sina, Al-Farabi and Ikhwanus Shafa) - Faizatul Husna (Amandemen: Journal of Learning, Teaching and Educational Studies, 2024)
In this writing will be explained about the thought figures of Ibn Sina, Al-Farabi and Ikhawanus Shafa is about Islamic Education. And a little explains some things related to Ibn Sina, Al-Farabi and Ikhwanus Shafa such as the biography of Ibn Sina, Al-Farabi and Ikhwanus Shafa and the thoughts of these three figures about Islamic education. This study aims to examine the thoughts of Ibn Sina, Al-Farabi and Ikhwanus Shafa towards Islamic Education. This research is a descriptive qualitative research using the type of literature study research (libraray research) and the method used is documentation data collection and content analysis.  Ibn Sina is one of the Muslim thinkers who mastered the most various scientific fields. The thought of Islamic Education according to Ibn Sina is an effort to form a perfect human being, namely in physical (physical), intellectual (preparing professional energy), and ethics (moral) development. While Al-Farabi is a Muslim philosopher who has a great influence on the thought of the eastern world and also the western world, and the thought of Islamic Education According to the figure of Al-Farabi, education is a means or container to acquire a series of values, knowledge and skills in a certain time and culture.  And lastly, the Ikhwanus Shafa is a secret society engaged in science which consists of several young people. Islamic Education Ikhwanus Shafa thought about the concept of educational goals, namely by formulating individual and social goals by realizing them through educational activities by giving more portion to social goals than individual goals.